Desarrollo de un geovisor para contribuir en la toma de decisiones y la gestión de riesgos naturales y socioambientales de las instituciones educativas públicas en el departamento del Atlántico (2024)
In recent decades, Colombia has faced a significant increase in natural disasters, which has shown the poor preparation of the territories to effectively confront the effects of climate phenomena. Educational institutions on the Atlantic coast are exposed to different natural threats that generate interruptions in educational services and health problems, putting the comprehensive development and safety of the student community at risk. For this reason, it is crucial to have preventive measures, generate knowledge and prepare the educational community to face emergencies. It is necessary to have a tool that allows the visualization of risks in institutions that favors decision-making and preventive measures. The main objective of this research is to develop a geovisor that contributes to decision-making and the management of natural and socio-environmental risks of educational institutions in the department of Atlántico. To carry out this study, the risk assessment adopted by the Atlantic Regional Corporation (CRA) was taken into account, which is based on the risk matrix of interrelation between the probability and impact of occurrence to determine its classification. taking into account the individual context of each institution. The results showed that the most relevant threat is windstorms due to their greater significance in the community, on the other hand, the eastern subregion is identified as the one that presents the highest vulnerability index due to its high population concentration, followed by the coastal subregion, which presents the result with the highest average level of risk in the department, however, it has the lowest number of educational institutions therefore a lower number of exposed students.